Drug‐induced anaphylactic reactions in children: A retrospective analysis of 159 validated spontaneous reports. Issue 3 (31st January 2019) - Sachs, Bernhardt; Dubrall, Diana; Fischer‐Barth, Wilma; Schmid, Matthias; Stingl, Julia
Abstract: Purpose: The main objective of this study was to analyze validated cases of drug‐induced anaphylactic reactions in children with regard to incriminated drugs, clinical characteristics, and associated factors. A further objective was to compare differences in incriminated drugs and characteristics between validated cases and a reference excluding anaphylactic reaction cases (basic dataset). Methods: Spontaneous reports of anaphylactic reactions in children (0‐17 years) registered between January 2000 to December 2016 were extracted from the adverse drug reaction database of the German Federal Institute for Drugs and Medical Devices. These reports were restricted to drugs for which at least four cases were found. After case validation, 159 reports remained (validated dataset) and were compared with the basic dataset (n = 12.168 reports) using inferential statistics. Results: Estimated yearly increase of reports (36.8 vs 0.1), most frequently incriminated drugs (antibiotics 30.2% vs 11%, analgesics/antipyretics 22.0% vs 5.6%; P values less than 0.001) and route of administration (38.4% vs 6.7%) differed between the validated dataset and the basic dataset. Validated cases differed in severity (higher with atracurium), reported symptoms (urticaria leading with analgesics), and associated factors (atopy/allergy rarely reported with antibiotics) depending on the incriminated drug class. In 13.8% (11.3% if excluding repeated readministration in one person) of the cases, the drug had not been tolerated before. Conclusions: A heterogeneous clinical phenotype with differences in associated factors was observed, suggesting different underlying mechanisms triggered by the different drug groups. Occurrence of serious drug‐induced anaphylactic reactions in children could be reduced by carefully considering patient history.